2020
DOI: 10.1098/rsos.200173
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane-induced demographic changes in a non-human primate population

Abstract: Major disturbance events can have large impacts on the demography and dynamics of animal populations. Hurricanes are one example of an extreme climatic event, predicted to increase in frequency due to climate change, and thus expected to be a considerable threat to population viability. However, little is understood about the underlying demographic mechanisms shaping population response following these extreme disturbances. Here, we analyse 45 years of the most comprehensive free-ranging non-human primate demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 53 publications
(83 reference statements)
7
46
0
Order By: Relevance
“…In this way, variation in individual quality may mask expected trade‐offs (McLean et al, 2019 ). Although major hurricanes are known to have immediate effects on the mean annual fertility of these females, they have no effects on annual survival, a finding that motivated hypotheses about the potential optimization of life histories by means of ensuring survival on a bad year at the cost of reproduction (Morcillo et al, 2020 ). Finally, our analysis showed that experiencing a hurricane early in life slightly increased the chances of having an LRS equal to 0.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this way, variation in individual quality may mask expected trade‐offs (McLean et al, 2019 ). Although major hurricanes are known to have immediate effects on the mean annual fertility of these females, they have no effects on annual survival, a finding that motivated hypotheses about the potential optimization of life histories by means of ensuring survival on a bad year at the cost of reproduction (Morcillo et al, 2020 ). Finally, our analysis showed that experiencing a hurricane early in life slightly increased the chances of having an LRS equal to 0.…”
Section: Discussionmentioning
confidence: 99%
“…Hurricanes Hugo and Georges were category 3 hurricanes when their centers were closest to the CSFS (~23 and ~8.4 km from CSFS, respectively). These hurricanes exhibited sustained wind speeds of approximately 201 and 185 km h −1 , respectively, with hurricane‐force winds extending over the entire field station (Morcillo et al, 2020 ). Both hurricanes produced severe damage to Cayo Santiago's vegetation, with 60–90% canopy loss following each hurricane (Morcillo et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations